(untitled) (Economics and region, 2025)
An analysis of economic security in Ukraine shows that the situation has significantly deteriorated not only at the national level, but also at the business level. Risks and threats accompany all components of the functional and structural decomposition of economic security: financial (due to the instability of the national currency), investment and innovation (due to a significant deterioration in the investment attractiveness of Ukrainian business), intellectual and human resources (due to the mass migration of the economically active population abroad, conscription and service in the defense of Ukraine by qualified, highly intellectual citizens of Ukraine), technical and technological (due to constant destruction as a result of missile and shahid strikes, mining), information (due to the aggressor’s intensification of information warfare and the spread of disinformation, frequent hacker attacks), institutional and legal (due to military actions, frequent changes in the provisions of current legislation), environmental (due to environmental pollution), and physical (due to destruction). It is argued that the level of intellectual capital and the actions of a professional business or government team largely determine the level of all components of economic security. The main ideas presented in the book by Italian historian and economist Carlo M. Cipolla, The Laws of Human Stupidity, are analyzed, and it is concluded that there is an intellectual and personnel threat in the economic security system. This threat is the real or potential destructive actions of employees-individuals who disrupt the normal economic condition of a business entity and are capable of causing great harm for personal gain (thieves) or without personal gain (fools). It is believed that practical solutions to business economic security problems related to ineffective personnel policy require the development and implementation of appropriate management tools, in particular, a human resource management strategy. After all, practical solutions to economic security issues depend on the degree of mastery of strategic management methodologies and methods. The concept of Hubert K. Rampersad’s “Universal Performance Measurement System” is considered, which addresses issues of business improvement based on changes in the collective and individual behavior of employees. This system is based on self-management, self-development, and self-coaching, which should be inherent not only in managers but also in ordinary employees of the enterprise. An important tool for employee self-training is the Kolb learning cycle – a process of intuitive learning or learning by doing. A new theoretical approach to management has been substantiated, focusing on the continuous training and development of enterprise employees. This will ensure long-term success, take into account the interests of stakeholders, overcome internal threats to the economic security of the business, and successfully predict and minimize the impact of external threats.